Symptoms and quality of life in patients with suspected angina undergoing CT coronary angiography: a randomised controlled trial. Issue 13 (28th February 2017) - Williams, Michelle C; Hunter, Amanda; Shah, Anoop; Assi, Valentina; Lewis, Stephanie; Mangion, Kenneth; Berry, Colin; Boon, Nicholas A; Clark, Elizabeth; Flather, Marcus; Forbes, John; McLean, Scott; et al.
Abstract : Background: In patients with suspected angina pectoris, CT coronary angiography (CTCA) clarifies the diagnosis, directs appropriate investigations and therapies, and reduces clinical events. The effect on patient symptoms is currently unknown. Methods: In a prospective open-label parallel group multicentre randomised controlled trial, 4146 patients with suspected angina due to coronary heart disease were randomised 1:1 to receive standard care or standard care plus CTCA. Symptoms and quality of life were assessed over 6 months using the Seattle Angina Questionnaire and Short Form 12. Results: Baseline scores indicated mild physical limitation (74±0.4), moderate angina stability (44±0.4), modest angina frequency (68±0.4), excellent treatment satisfaction (92±0.2) and moderate impairment of quality of life (55±0.3). Compared with standard care alone, CTCA was associated with less marked improvements in physical limitation (difference −1.74 (95% CIs, −3.34 to −0.14), p=0.0329), angina frequency (difference −1.55 (−2.85 to −0.25), p=0.0198) and quality of life (difference −3.48 (−4.95 to −2.01), p<0.0001) at 6 months. For patients undergoing CTCA, improvements in symptoms were greatest in those diagnosed with normal coronary arteries or who had their preventative therapy discontinued, and least in those with moderate non-obstructive disease or had a new prescription of preventative therapy (p<0.001 for all). Conclusions: While improving diagnosis, treatment and outcome, CTCA is associated with a small attenuation of the improvements in symptoms and quality of life due to the detection of moderate non-obstructive coronary artery disease. Trial registration number: NCT01149590.